Criminal Acts of Banging and Assault in Positive Law in Aceh Tamiang (Analysis of Decision Number: 216/PID.B/2021/PN.KSP) - Zulkifli, Zulkifli; Zarzani, T. Riza (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The criminal acts of assault and ganging up have become prevalent in many communities, including Aceh Tamiang, where such acts often result in serious injury or even death. This research analyzes case number 216/Pid.B/2021/PN KSP, in which the defendant, Riski Efendi, along with other perpetrators, committed violent assault. The defendant was sentenced to 1 year and 6 months in prison under Article 170 of the Indonesian Criminal Code for collective violence. The legal analysis highlights the regulations surrounding such offenses, including Articles 170 and 358 of the Criminal Code, which regulate collective violence and the role of joint action in violent crimes. The decision of the court was based on legal evidence that clearly supported the guilt of the defendant, considering the physical injuries inflicted on the victim. This study also reflects on the limitations of current legal enforcement, suggesting that restorative justice approaches might have been more appropriate in resolving the dispute. The research underscores the importance of adequate law enforcement to deter mob violence and ensure justice.